Inventário de forma compartilhada: percurso para aproximar comunidades do seu patrimônio cultural - Camila Iris Corrêa (2018)
This research was conceived from the question of how the school can contribute to narrow the dialogue of local museums with their respective communities. Having as a theoretical and conceptual basis the foundations of New Museology, mainly in what concerns the relation of the subjects with the cultural patrimony, and the premises of the patrimonial and museal education, a methodology of Shared Inventory was delineated, to be used in the classroom as an educational resource for exploring urban cultural heritage. The historical construction of the idea of the museum and the concept of heritage, the potential of musealization that the city can offer and the experiences that have been used in the renewed and expanded perspective Inventory surpassing the unique and exclusive domain of the specialists are analyzed. This theoretical and empirical framework allowed to carry out a study on the use of Shared Inventory as a socially inclusive pedagogical tool, thus seeking a way to establish connections between the school community, the cultural heritage in the city and the local museum. The construction of the Inventory took the form of a classroom experiment of an EJA class, which made it possible to test and evaluate the educational potential of the method. The results are systematized in a product - Shared Inventory: A Heritage Education Guide-